Adsorption cycle "heat from cold" for upgrading the ambient heat: The testing a lab-scale prototype with the composite sorbent CaClBr/silica. (1st February 2018) - Tokarev, Mikhail M.; Gordeeva, Larisa G.; Grekova, Alexandra D.; Aristov, Yuri I.
Highlights: A new adsorption cycle HeCol for upgrading the ambient heat is studied. Heat source with low temperature of 2–30 °C is used to get the useful heat at 35–50 °C. The HeCol feasibility is demonstrated for the first time on a lab-scale prototype. The composite methanol sorbents exchanging up to 0.46 g/g are prepared for HeCol cycle. The maximum specific heating power in HeCol cycle equals 1.4–3.6 kW/kg of the sorbent. Abstract: Adsorptive transformation of heat is an emerging technology that is especially promising for low-temperature heat sources. Recently, an adsorption cycle (the so-called "Heat from Cold" or HeCol) has been suggested for upgrading the ambient heat in cold countries. This paper addresses the selection of composite sorbents of methanol specialized for this cycle and the study of their sorption properties. First, we analyzed which adsorbent is optimal for the HeCol cycle and how its properties depend on the HeCol cycle boundary temperatures. Then, three composite sorbents, based on CaCl2, CaBr2 and their mixture confined inside the silica gel mesopores, were prepared and their sorption equilibrium with methanol was analyzed keeping in mind the HeCol cycles with various boundary temperatures. It was shown, that these composite sorbents exchange up to 0.48 g of methanol per 1 g of the composite that far exceeds this value for common activated carbons. Finally, a first lab-scale HeCol prototype was built and tested with one of the studied sorbents, namely CaClBr/SiO2, to evaluate the feasibility of the cycle.